2011
DOI: 10.5334/pb-51-3-4-237
|View full text |Cite
|
Sign up to set email alerts
|

The Convergence of Alexithymia Measures

Abstract: The construct of alexithymia is most frequently measured by means of the 20-item Toronto Alexithymia Scale . However a number of other instruments have been developed to compensate for problems with measuring alexithymia through self-report measures. Convergence between the different alexithymia measures is rarely studied. This study investigates the convergence among the TAS-20, the Observer Alexithymia Scale (OAS), the Toronto Structured Interview for Alexithymia (TSIA), the modified Beth Israel Hospital Psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…The correlation of r ¼.45 between self-report (TAS-20) and observer-rated (TSIA) measure of alexithymia in the current study is comparable with correlations found in other studies in which TAS-20 and TSIA have been administered. Bagby et al (2006), for example, reported a correlation of r¼ .36 in normal participants, whereas correlation coefficients of r ¼.34 (Inslegers et al, 2013), r ¼ .49 , or r ¼47 (Meganck et al, 2011) have been observed in patient samples. Caretti et al (2011) reported a correlation of r ¼.44 in a mixed sample of patients and healthy controls.…”
Section: Assessment Of Alexithymiamentioning
confidence: 84%
“…The correlation of r ¼.45 between self-report (TAS-20) and observer-rated (TSIA) measure of alexithymia in the current study is comparable with correlations found in other studies in which TAS-20 and TSIA have been administered. Bagby et al (2006), for example, reported a correlation of r¼ .36 in normal participants, whereas correlation coefficients of r ¼.34 (Inslegers et al, 2013), r ¼ .49 , or r ¼47 (Meganck et al, 2011) have been observed in patient samples. Caretti et al (2011) reported a correlation of r ¼.44 in a mixed sample of patients and healthy controls.…”
Section: Assessment Of Alexithymiamentioning
confidence: 84%
“…First, we relied exclusively on self-reported measures. The literature suggests that multi-method assessments (e.g., self-reporting, interviews and observation) should be used when measuring alexithymia, to minimize measurement errors (e.g., Meganck, Inslegers, Vanheule, & Desmet, 2011;Taylor & Bagby, 2004;Waller & Scheidt, 2004). Moreover, it is arguable that the way people represent and regulate emotions is, to an important extent, implicit (e.g., Westen & Blagov, 2007).…”
Section: Limitationsmentioning
confidence: 99%
“…Moreover, a Dutch study in a clinical population is the first -to our knowledge -that examined the convergence between more than two alexithymia measures simultaneously (Meganck, Inslegers, Vanheule, & Desmet, 2011). In this study an exploratory factor analysis was conducted of the subscales of four alexithymia measures [TAS-20, TSIA, Observer Alexithymia Scale (OAS;Haviland, Warren, & Riggs, 2000), modified Beth Israel Hospital Psychosomatic Questionnaire (mBIQ; ] and four facets of the alexithymia construct rated by the treating psychologist.…”
Section: Introductionmentioning
confidence: 99%